Halal Certification Management in Indonesia - Maliha, Hasna; Devi, Abrista (SMART Insight, 2023)
This study seeks to map research related to halal certification in Indonesia published by Dimensions indexed journals from 2015 to 2023. NVivo 12 Plus was used to conduct thematic studies and frequency was used to evaluate 91 publications in the scientific literature. The results found that the number of publications fluctuates from year to year related to halal certification research in Indonesia, which indicates that this topic is an interesting topic and must continue to be developed. In addition, various focuses of discussion and cluster analysis that describe research paths in halal certification research in Indonesia include Halal Certification Process in Indonesia, Halal Product and Halal Certification in Indonesia, Halal food and Halal Certification in Indonesia, International Trade and Halal Certification in Indonesia, Halal Certification System and Halal Certification in Indonesia, and Industry and Halal Certification in Indonesia.This research can be used as a starting point for experts to build a graphical visualization of halal certification research patterns in Indonesia in published scientific research